Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1073/pnas.2112630119
|View full text |Cite
|
Sign up to set email alerts
|

A peptide toxin in ant venom mimics vertebrate EGF-like hormones to cause long-lasting hypersensitivity in mammals

Abstract: Venoms are excellent model systems for studying evolutionary processes associated with predator–prey interactions. Here, we present the discovery of a peptide toxin, MIITX2-Mg1a, which is a major component of the venom of the Australian giant red bull ant Myrmecia gulosa and has evolved to mimic, both structurally and functionally, vertebrate epidermal growth factor (EGF) peptide hormones. We show that Mg1a is a potent agonist of the mammalian EGF receptor ErbB1, and that intraplantar injection in mice causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…Finally, we employed a strategy related to that of Eagles and colleagues [ 31 ] by initiating a BLAST search to identify patterns of similarity between ant EGF-like toxins and known EGF hormones across the animal kingdom ( Table 2 ). We found that five major subgroups of EGF-like toxins exist in ants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, we employed a strategy related to that of Eagles and colleagues [ 31 ] by initiating a BLAST search to identify patterns of similarity between ant EGF-like toxins and known EGF hormones across the animal kingdom ( Table 2 ). We found that five major subgroups of EGF-like toxins exist in ants.…”
Section: Resultsmentioning
confidence: 99%
“…The 113 venom components in M. ruginodis included two peptides with an EGF-like motif. These form part of a diverse family of metazoan peptide hormones that are also venom components in anemones and ants [ 14 , 22 , 31 , 46 , 47 ]. EGF-like peptides therefore provide another example of the “toxipotent” nature of peptide hormones and their potential to become weaponized as venom components [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations